Genre Analysis of Online Promotion on Nihi Tourism Website - Lestari, Vici Diniyah; Ekawati, Rosyida (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
This study aims to investigate the moves and steps leading to the generic structures of Nihi Official Website. It is a descriptive qualitative method. The source of data in this study is the official website of Nihi, while the data are the sentences in promotional of tourism destination that contain of move and step of advertisement. It is based on Bhatia’s (1993) moves and steps in advertisements. The results of the study shows that there are four obligatory moves, i.e. move 1 establishing credentials, move 2 introducing the offer with 2 steps in move 2, namely step 1 offering the product and step 2 essential detailing of the offer, move 5 soliciting responses. There is a non-obligatory, i.e. move 6 pressure tactic that only appear once. In addition, there are absences of three moves. They are move 3, move 4, and move 7 that are not found the promotional website.